2013
DOI: 10.1161/atvbaha.113.301819
|View full text |Cite
|
Sign up to set email alerts
|

Is There a New Target in the Renin–Angiotensin System for Aortic Aneurysm Therapy?

Abstract: A ortic aneurysm and aortic dissection are important causes of mortality, which are principally managed by surgical interventions.1-3 The absence of specific medications which can limit the complications of these important aortic pathologies has stimulated an intense interest in studying the mechanisms underlying these diseases.1-3 A major focus of these studies has been the renin-angiotensin system. Angiotensin II has been linked to aortic aneurysm and dissection on the basis of evidence from a range of studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Histological evidence of aortic dissection was also demonstrated in 40% of the mice. While aneurysm induction was associated with hypertension, the rise in blood pressure induced was not correlated with the size or incidence of aneurysm development [10], [19]. Our study provides the first evidence in older men, who are most at risk of AAA, that, similar to rodents, salt intake is associated with AAA.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Histological evidence of aortic dissection was also demonstrated in 40% of the mice. While aneurysm induction was associated with hypertension, the rise in blood pressure induced was not correlated with the size or incidence of aneurysm development [10], [19]. Our study provides the first evidence in older men, who are most at risk of AAA, that, similar to rodents, salt intake is associated with AAA.…”
Section: Discussionmentioning
confidence: 52%
“…The common feature of all these rodent model studies appears to be the administration of salt along with activation of a part of the renin-angiotensin-aldosterone system [19]. Raised blood pressure is another common feature of these models however lowering blood pressure does not necessarily inhibit aneurysm formation [10], [11], [19]. These findings are in keeping with our observation that higher salt intake was associated with AAA independently of a history of hypertension or treatment for hypertension and measured mean blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liu et al . [49] demonstrated that aldosterone can provoke aneurysm formation independently of AngII related mechanisms [49,50]. …”
Section: Pathological Mechanisms Of Aaa Developmentmentioning
confidence: 99%
“…Multiple studies have indicated that the RAAS contributes to human AAA pathogenesis, as the enzymes involved in ANG II formation are upregulated in human AAA tissue (25,62,137,178). Furthermore, the RAAS is involved in vascular remodeling and inflammation seen in animal models of AAA pathogenesis (25,56). Thus, many in vivo studies have implemented chronic infusion of ANG II in ApoE Ϫ/Ϫ mice to model human AAA pathology (23,24,158).…”
Section: Sex Differences In the Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%